2021
DOI: 10.1038/s41598-020-79822-w
|View full text |Cite
|
Sign up to set email alerts
|

Decreased cortisol among hikers who preferentially visit and value biodiverse riparian zones

Abstract: While outdoor recreationists often report increases to their well-being for time spent in nature, the mechanisms through which local ecologies affect human health have been difficult to quantify, and thus to manage. We combine data from pre-post salivary cortisol measures, GPS tracks, visitor photos, and surveys from 88 hikers traversing several types of landscape within peri-urban public lands in southwest Idaho, USA. We find that time in biodiverse riparian areas and areas of perceived aesthetic value correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The respondents' answers signal that the majority of surveyed people were drawn to riverine forests mainly to enjoy nature while having a walk (Figure 2), which simultaneously provided them with several benefits-aesthetic experiences, stress reduction, and physical activities [3,23]. Having walks and hikes in biodiverse riparian areas and forests alongside streams and rivers has been proven to reduce salivary cortisol levels and improve the overall well-being of hikers [12]. Furthermore, natural riparian areas and wildlife sightings have also been associated with aesthetic and travel preferences among residents [12].…”
Section: Recreational Habits and Frequencymentioning
confidence: 99%
See 2 more Smart Citations
“…The respondents' answers signal that the majority of surveyed people were drawn to riverine forests mainly to enjoy nature while having a walk (Figure 2), which simultaneously provided them with several benefits-aesthetic experiences, stress reduction, and physical activities [3,23]. Having walks and hikes in biodiverse riparian areas and forests alongside streams and rivers has been proven to reduce salivary cortisol levels and improve the overall well-being of hikers [12]. Furthermore, natural riparian areas and wildlife sightings have also been associated with aesthetic and travel preferences among residents [12].…”
Section: Recreational Habits and Frequencymentioning
confidence: 99%
“…Having walks and hikes in biodiverse riparian areas and forests alongside streams and rivers has been proven to reduce salivary cortisol levels and improve the overall well-being of hikers [12]. Furthermore, natural riparian areas and wildlife sightings have also been associated with aesthetic and travel preferences among residents [12]. Berry and mushroom picking are other activities that were rather popular among the respondents, as previous research in 2010 indicated that around 77% of the inhabitants of Latvia had gone to forests in order to gather one of these goods [24] and Respondents' attitude (concerned/ not concerned) towards proposed issues related to the state of rivers and riverine forests.…”
Section: Recreational Habits and Frequencymentioning
confidence: 99%
See 1 more Smart Citation